Comprehensive Psychological Assessment of Individuals with Organic Mood (Affective) Disorder - Ziana Isniahangga Hidayah; Qurrota A’yuni Fitriana (International Conference on Psychology and Education (ICPE), 2025)
Mental health is a crucial aspect of an individual's well-being, often influenced by biological, psychological, and social factors. This case study focuses on organic mood (affective) disorder in adolescents, with a focus on causal factors stemming from physical conditions, namely hyperthyroidism disorders and systemic brain damage. A qualitative case study method was used, involving in-depth interviews and observations over three months to collect comprehensive data on the patient's history and the variables influencing their condition. The results indicate that the patient's organic mood (affective) disorder is closely related to hyperthyroidism, which impacts emotional stability and behavior. Lack of knowledge about access to healthcare with a dysfunctional family background, significantly worsens the patient's condition. These results demonstrate that organic mental disorders are shaped by a complex interaction between biological, psychology, and social factors. These findings highlight the importance of increasing public and healthcare professional awareness of the importance of early detection of physical conditions that affect mental health, as well as the need for a comprehensive treatment approach to improve the quality of life of individuals with organic mood (affective) disorders.